Evaluation of soil and water properties in relation to indicative rice productivity in the coastal fields of Pangandaran, West Java, Indonesia - Nasrudin, Nasrudin; Kurniasih, Budiastuti; Putra, Eka Tarwaca Susila; Hanudin, Eko (Journal of Degraded and Mining Lands Management, 2026)
Coastal rice fields often have sandy textures, high salinity, low organic matter, and frequent waterlogging caused by seawater intrusion. These conditions, together with fluctuating rainfall, alter soil chemical properties and negatively affect crop cultivation. This study aimed to evaluate soil chemical properties, assess water quality, and analyze their relationship with rice productivity in the coastal rice fields of Pangandaran, West Java, Indonesia. Composite soil samples were collected from areas of 5-7 ha and analyzed for their chemical properties. Water quality was assessed based on the levels of dissolved oxygen (DO), nitrate, phosphate, electrical conductivity (EC), and pH. Data were analyzed descriptively, and Principal Component Analysis (PCA) was applied to group the sampling points. The results showed that organic C and total N were low to moderate, while available-Si and exchangeable K+ were very low. In contrast, P?O?, exchangeable Na+, and exchangeable Mg2+ were very high, whereas cation exchange capacity (CEC) and exchangeable Ca2+ were low to moderate. Based on EC and water table depth, PCA grouped the 20 sampling points into three clusters: high salinity (points 16-19), waterlogging (points 2-7), and relatively normal conditions (points 1, 8-15, 20). Average rice productivity was 2.48 t ha-1 in cluster 1, less than 1 t ha-1 in cluster 2, and 3,63 t ha-1 in cluster 3. These findings highlight the need for site-specific land and water management strategies to sustain rice cultivation in coastal areas.